Impact of traumatic dental injuries on quality of life in preschoolers and schoolchildren: A systematic review and meta‐analysis. Issue 1 (21st September 2017) - Zaror, Carlos; Martínez‐Zapata, María José; Abarca, Jaime; Díaz, Jaime; Pardo, Yolanda; Pont, Àngels; Ferrer, Montse
Abstract: Objectives: Traumatic dental injuries (TDIs) in childhood and adolescence are a potential public health problem given their prevalence and consequences. The aim of this study was to assess the impact of TDIs on the oral health‐related quality of life (OHRQoL) of preschoolers and schoolchildren, by synthesizing the available evidence. Methods: A systematic search was conducted in MEDLINE, EMBASE, Cochrane, ScieLo and Lilacs databases since January 1966 until March 2016. The included studies compared OHRQoL between groups with and without TDIs, using validated instruments. The selection process and data extraction were carried out by two researchers independently. A third reviewer resolved discrepancies. Methodological quality was assessed with the Effective Public Health Practice Project's Quality Assessment Tool. Meta‐analyses were performed using random effect models, separately for preschoolers and schoolchildren. Results: Of 213 identified articles, 26 studies (involving a total of 4582 patients and 13 601 controls between the ages of 1 and 15 years) met the inclusion criteria. Most of the studies had been published in the last 5 years, and their methodological quality was judged to be moderate. The TDIs group had a significantly higher chance of reporting any impact on OHRQoL than controls for both preschoolers (OR = 1.44; 95% confidence interval [CI]: 1.28‐1.63; I 2 = 0%) and schoolchildren (OR = 1.31; 95% CI: 1.04‐1.66; I 2 = 70%). In preschoolers, the OR for OHRQoL impact for complicated vs uncomplicated TDIs was 1.53 (95% CI: 1.04‐2.26; I 2 = 0%). The social domain was the most affected one in schoolchildren (standard mean difference = 0.34; 95% CI: 0.13, 0.55; I 2 = 68%). Conclusion: Traumatic dental injuries have a negative impact on OHRQoL of both preschoolers and schoolchildren. Outcome standardization to measure OHRQoL impact, such as mean score differences and cut‐off points, is needed. Prospective cohort studies are recommended to confirm these findings and to understand how TDIs' impact changes with time.